Synthesis, antimicrobial activity and absorption studies of some novel heterocyclic dyes based on 4-hexylbenzene-1,3-diol - Patel, Hitendra Mangubhai (European Journal of Chemistry, 2012)
Aniline derivatives were diazotized and coupled with 3-aminocrotononitrile to give the corresponding 2-arylhydrazono-3-ketiminobutyronitriles. Cyclization of these arylhydrazono derivatives with hydrazine monohydrate afforded 5-amino-4-arylazo-3-methyl-1H-pyrazoles which were subsequently diazotized and coupled with malononitrile to yield a series of pyrazolylhydrazonomalononitriles. These compounds were then reacted with hydrazine monohydrate to provide, heterocyclic dyes, which were further diazotized and coupled with 4-hexylbenzene-1,3-diol to produce novel heterocyclic tetraazo dyes which were characterized by elemental analysis and spectral methods. The antimicrobial activity and absorption characteristics of the dyes were also examined in detail.